2013 IEEE International Conference on Robotics and Automation 2013
DOI: 10.1109/icra.2013.6630804
|View full text |Cite
|
Sign up to set email alerts
|

Design of a micro-cartridge system for the robotic assembly of exchangeable AFM-probe tips

Abstract: Modern processes of micro-and nanofabrication imply several metrology steps on critical dimensions in order to assure and assess device perfomences. Particularly, manufacturing processes of novel disruptive photonic devices and nanoelectronic circuit architectures require improved three dimensional acquisition and visualization techniques for their metrology. Amongst others line width and sidewall roughness are the most important parameters for nanooptical components but the determination of these parameters b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our earlier work showed that standard lateral nanolithography, which is much more rapid, flexible and effective than vertical, on-axis processing in terms of defining topology, could be used to fabricate customizable scanning probe tips [27], and that such tips can be integrated with AFM probes equipped with special connectors through semiautomatic robotic nanomanipulation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier work showed that standard lateral nanolithography, which is much more rapid, flexible and effective than vertical, on-axis processing in terms of defining topology, could be used to fabricate customizable scanning probe tips [27], and that such tips can be integrated with AFM probes equipped with special connectors through semiautomatic robotic nanomanipulation [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…canning electron microscopy (SEM), which enables highresolution imaging of micro/nano-scale objects, is a common tool for micro/nano-robotics development 1 . For example, previous work has demonstrated the use of SEM for assembling [2][3][4] , handling and characterizing nanomaterials [5][6][7][8] , nanowires, carbon nanotubes, and other nanoscale objects 9,10 . In addition, optical microscope (OM) has been widely integrated with micro-robotic systems.…”
mentioning
confidence: 99%